Hybrid Approach to Manage Inflammatory Internal Root Resorption: A Case Report - Mirzaei, Arezoo; Zargar, Nazanin; Shahhosseini , Rezvan (Iranian Endodontic Journal, 2025)
Internal inflammatory root resorption (IRR) poses significant challenges in endodontic treatment due to its potential to compromise tooth integrity. This case report describes the conservative management of IRR in a 40-year-old woman with a radiolucent lesion in the midroot of a maxillary central incisor. Early diagnosis using cone-beam computed tomography prevented perforation and guided treatment planning. Non-surgical endodontic treatment was performed using a dental operating microscope, ultrasonic irrigation, and a hybrid obturation technique. The apical portion of the canal was sealed with a bioceramic sealer and single-cone gutta-percha, while the resorptive defect was filled with calcium-enriched mixture cement due to its biocompatibility and sealing properties. At one-year follow-up, the patient was asymptomatic, with radiographic evidence of healing. This case highlights the efficacy of combining advanced diagnostic tools, bioactive materials, and minimally invasive techniques for successful IRR management.